Orexin-A and motion sickness: a systematic review of animal model studies - Cai, Xu; Zhao, Long; Wang, Xin; Chen, Jiahui; Yuan, Ying; Gao, Biao; You, Yanli (Frontiers in Pharmacology, 2025)
BackgroundSensory input mismatches among the vestibular system, autonomic control, and visual perception cause motion sickness. Anticholinergics and antihistamines are commonly used but have limited efficacy and cause significant side effects. Orexin-A, a hypothalamic neuropeptide, has recently garnered attention for its potential role in controlling motion sickness.ObjectiveTo summarize current knowledge on the effects and mechanisms of orexin-A in reducing motion sickness, identify gaps, and propose future research directions.MethodsFive qualified animal experiments were identified after searching PubMed, Scopus, Cochrane Library, Embase, and WoS. The SYRCLE tool was used to evaluate study quality, followed by a qualitative synthesis.ResultsOrexin-A reduced motion-induced behavioral abnormalities, nausea, and vomiting in rat and cat models. These benefits are likely mediated by the modulation of hypothalamic nuclei activity, enhanced stomach motility, and improved vestibular function. However, several limitations were observed, including inadequate reporting on randomization, blinding, and allocation concealment, as well as heterogeneity in interventions and outcome measures.ConclusionAnimal model studies indicates that orexin-A mitigates motion sickness (MS) symptoms in animal models, but overall certainty is low to moderate owing to risk of bias and indirectness. Rigorous, blinded studies with standardized outcomes—and ultimately, early-phase clinical trials, are needed to clarify therapeutic potential.